Raman spectroscopy and microscopy of electrochemically and chemically doped high-mobility semiconducting polymers. Issue 25 (7th June 2017) - Francis, C.; Fazzi, D.; Grimm, S. B.; Paulus, F.; Beck, S.; Hillebrandt, S.; Pucci, A.; Zaumseil, J.
Abstract : Raman spectra and DFT calculations show that p-doping of two semiconducting polymers affects mostly their electron-rich thienothiophene units. Abstract : The polaronic nature of two high-mobility hole-conducting polymers (PBTTT and DPPT-TT) is investigated by Raman spectroscopy and density functional theory (DFT) calculations. Chemical and electrochemical hole doping of these polymers leads to characteristic changes in the intensity ratios of the Raman active CC stretching modes but no significant frequency shifts. The data indicate a localization of positive polarons on the electron-rich thienothiophene cores that are present in both polymers. DFT calculations show that the Raman intensity ratio variations are most likely caused by the local electric field that originates from negatively charged dopant molecules or electrolyte anions and the positive polaron on the polymer chain. The characteristic changes in the Raman mode intensity ratios with the degree of doping enable in situ mapping of charge carrier concentration in the channel of electrolyte-gated polymer transistors with high spatial resolution.